For a global history of penal colonies and convict labor - Beattie, Peter M. (Esboços: histories in global contexts, 2021)
Review of: ANDERSON, Clare (ed.). A Global History of Convicts and Penal Colonies. London: Bloomsbury Academic, 2020. 408 p.